Cost effective factor of a Midimew connected Mesh Network - Rahman, M.M. Hafizur; Mohd. Nor, Rizal; Akhand, M. A. H; Sembok, Tengku Mohd (2016)
Hierarchical Interconnection network (HIN) is very much essential for the practical implementation of future generation massively parallel computers (MPC) systems which consists of millions of nodes. Because it yields better performance with low cost due to reduction of wires and by exploring the locality in the communication & traffic patterns. A Midimew connected Mesh Network (MMN) is an HIN comprised of numerous basic modules, where the basic modluea are 2D-mesh networks and they are hierarchically interconnected using midimew network to assemble the higher level networks. In this paper, we present the architecture of a MMN and evaluate the cost effective factor of MMN, TESH, mesh, and torus networks. It is revealed that the proposed MMN yields a little bit high cost effectiveness factor with small diameter and average distance. Overall, performance with respect to cost effective factor with small diameter and average distance suggests that the MMN will be a promising choice for next generation MPC systems.